Working conditions as a risk factor for the health of employees of a metallurgical enterprise - Sharavara, L. P.; Dmytrukha, N. M.; Шаравара, Лариса Павлівна; Дмитруха, Н. М. (My University, 2024)
Introduction. The metallurgical industry is one of the leading manufacturing in Ukraine, where harmful production factors of various nature are present at the employees’ workplaces of various production sites, which increase the risk of developing occupational and production-related diseases. Aim. To carry out a hygienic assessment of the employees’ working conditions of a metallurgical enterprise as a risk factor for health. Materials and methods. A study of the production environment’s factors at the employees’ workplaces of the open hearth shop, blast furnace, and sintering workshops was conducted for the period from 2011-2021 based on the results of own research and scientific protocols: 2366 indicators of the industrial microclimate, 5761 indicators of air pollution in the working area, 220 indicators of industrial noise and vibration, 130 maps of working conditions to assess the difficulty and intensity of the labor process. The results. It was established, that the leading factors of the production environment at the workplaces of the workers of the sintering, open hearth and blast furnace shops include the production microclimate (class 3.4) and the content of industrial dust in the air of the working area (class 3.4). Also, in the air of the working area of all employees, there were chemicals that attribute working conditions to class 3.1−3.4 and industrial noise that exceeded the maximum permissible level and corresponds to 3.3 class of harm. Working conditions in all workshops correspond to class 3.1-3.3 in terms of labor difficulty and intensity. Working conditions at a metallurgical enterprise are characterized by a complex of unfavorable factors, which creates a high risk of occupational and productionrelated morbidity. Вступ. Металургійна галузь є однією з провідних галузей виробництва в України, де на робочих місцях працівників різних виробничих ділянок присутні шкідливі виробничі фактори різної природи, які підвищують ризик розвитку професійної та виробничо-зумовленої захворюваності. Мета. Провести гігієнічну оцінку умов праці працівників металургійного підприємства як фактору ризику для здоров’я. Об’єкт і методи дослідження. Проведено дослідження факторів виробничого середовища на робочих місцях працівників мартенівського, доменного та агломераційного цехів за період 2011-2021 рр. за результатами власних досліджень та протоколів дослідження: 2366 показників виробничого мікроклімату, 5761 показників забруднення повітря робочої зони, 220 показників виробничого шуму та вібрації, 130 карт умов праці для оцінки важкості та напруженості трудового процесу. Результати. Встановлено, що до провідних факторів виробничого середовища на робочих місцях працівників агломераційного, мартенівського та доменного цехів відноситься виробничий мікроклімат (3.4 клас) та вміст виробничого пилу у повітрі робочої зони (3.4 клас). Також, у повітрі робочої зони всіх працівників присутні хімічні речовини які відносять умови праці до 3.1−3.4 класу та виробничий шум, який перевищує гранично допустимий рівень і відповідає 3.3 класу шкідливості. Умови праці в усіх цехах за показниками важкості та напруженості праці відповідають 3.1−3.3 класу. Умови праці на металургійному підприємстві характеризуються комплексом несприятливих чинників, що формує високий ризик виникнення професійної та виробничо зумовленої захворюваності. Висновки. Отримані результати
Умови праці як фактор ризику для здоров’я працівників металургійного підприємства
Sharavara L. P. - https://orcid.org/0000-0001-9102-3686
Keywords: working conditions; professional risks; metallurgical enterprise; production factors; умови праці; професійні ризики; металургійне підприємство; виробничі чинники